Urban space living in a changing city: sidewalks of Curitiba / Espaço urbano viver numa cidade em mudança: calçadas de Curitiba - Faria, Helena Mendonça (2022)
This article aims to discuss the experience of the urban space, focusing on the conditions for pedestrian circulation, in the use of sidewalks, in Curitiba-PR, Brazil. In this city, as well as in the rest of the country, the use of public space is changing due to several factors, among them, the following stand out: the aging of the population and the greater participation of minority groups in decisions regarding public space, such as pedestrian groups. There was a problematic situation consisting of urban spaces designed primarily for automobiles, making it difficult for pedestrians to use such space or even preventing it in many cases. From this problem, it is questioned how the pedestrian, in three points of view, is using the sidewalks in Curitiba: a) the risks of being trampled; b) accessibility; and c) in terms of constructions and design quality. The assumption adopted is that the use of urban space by the pedestrian is a fundamental factor for sustainability by providing the practices of living and collective enjoyment of the same, by establishing relationships of sociability, physical exercises, recreation and leisure. The methodology used was based on the collection of information from municipal public agencies and bibliographical review of literature and academic research, using some categories of analysis: the public user; the building pattern; environmental conditions and municipal management practices. An analysis was made of the Strategic Plan of Sidewalks (PlanCal) of Curitiba and also the legislation regarding the construction and maintenance of public tours. The preliminary results showed that, in a city where the public transportation system was modeled on the Bus Rapid Transit (BRT) model, there is currently a high rate of individual motorization, the highest growth between 2001 and 2014 in the metropolitan Brazilian Regions areas, and an attention to the pedestrian that demands greater detailing and prioritization of work, investments and maintenance. Among the difficulties for the pedestrian are the following: the risks of being run over; low quality of accessibility; and problems in the execution and maintenance of the public tours, besides the need to expand the spaces destined to walking. This paper was originally published at Changing Cities 3rd International Conference on Changing Cities: Spatial, Design, Landscape & Socio-economic Dimensions- 2017. Here is published an update version.